Perkin-Elmer instruments in use at Hershey Company facility - Perkin-Elmer Corporation (1970)
General view of laboratory technician Margaret Kreiser using assorted Perkin-Elmer atomic absorption instruments at a Hershey Company facility to determine the metal constituents of finished food items and raw materials. Per notations accompanying the photograph, chocolate typically contains 12 metals in trace amounts.
Keywords: Women in science; Chocolate industry; Atomic absorption spectroscopy; Food--Analysis; Perkin-Elmer Corporation; Scientific apparatus and instruments; Hershey Company; Corporations; Women employees; Chocolate; Employees; Laboratories